Determinants of Stunting in Toddlers In Gatak Subdistrict, Sukoharjo Regency - johar, syefira ayudia; Sartika, Iik (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2023)
Indonesia faces nutritional problems that have an impact on the quality of human resources. One of the nutritional problems is the incidence of stunting experienced by more than half of stunting toddlers in the world who come from ASIA (55%). The highest number of stunting cases is based on e-PPGBM data for 2020-2021 in Sukoharjo Regency in Gatak District. In Gatak District, from 2020 to 2021, there has been an increase in stunting cases in toddlers. In 2020 in Gatak District, the number of stunted toddlers was 414 toddlers while in 2021 the number of stunted toddlers increased to 463 toddlers. This research is a quantitative research with a cross-sectional approach. The bound variables in this study are the incidence of stunting in toddlers, while the free variables in the study are maternal knowledge about nutrition, exclusive breastfeeding status, parental income, BBLR history and child care. The research sample was taken with a sampling quota with a total sample of 96 respondents who were toddlers in Gatak District, Sukoharjo Regency in 2021. The analysis used by researchers to determine the relationship of each variable using chi square analysis. The value of P is said to be related if the Value of P is <0.05. Based on the frequency distribution is mostly on productive age, higher education level, mostly employed, and income level is largely less than the UMR. There is a significant relationship between maternal knowledge, exclusive breastfeeding status, BBLR history and parenting with stunting events (p value = 0.000 < 0.05), while parental income has nothing to do with stunting events (p value = 0.067 > 0.05).